Slovenski anarhist Karel Anton Potisek v Salzburgu - Rozman, Franc (Zgodovinski časopis, 1986)
On the basis of the archive records the author describes the activity of the Slovene radical social democrat Karl Anton Potisek,who was in the years 1885-1888 politically active in the Worker's Cultural Society in Salzburg, persecuted, permanently changing his jobs. His example illustrates the destiny of most workers' agitators of that time. He is interesting for us because of the fact that he was a Slovene and unknown in the Slovene workers' movement.
Keywords: biografija; history of workers' movement; Potisek, K.A.; Slovenci; zgodovina delavskega gibanja